Are "Market Neutral" Hedge Funds Really Market Neutral? - Patton, Andrew J. (Review of Financial Studies, 2009)
[Using a variety of different definitions of "neutrality," this study presents significant evidence against the neutrality to market risk of hedge funds in a range of style categories. I generalize standard definitions of "market neutrality," and propose five different neutrality concepts. I suggest statistical tests for each neutrality concept, and apply these tests to a database of monthly returns on 1423 hedge funds from five style categories. For the "market neutral" style, approximately one-quarter of the funds exhibit significant exposure to market risk; this proportion is statistically significantly different from zero, but less than the proportion of significant exposures for other hedge fund styles.]